Leaf functional metabolic traits reveal the adaptation strategies of larch trees along the R/B ratio gradient at the stand level - Xiaoqian Song; Zhonghua Zhang; Haiyan Huang; Xin Guan; Lu Jin; Yu Shi; Wenjie Wang; Zhonghua Tang (Scientific Reports)
Abstract Light is crucial for understory sapling regeneration, and understanding leaf functional traits (LFT) is key to saplings’ adaptation to different light conditions. Currently, how LFT vary with light quality heterogeneity is not well understood. This study aims to assess canopy-induced light heterogeneity and the adaptive strategies of larch saplings to it. The study classified the light environments of larch saplings into three types based on red-to-blue light ratios: 0.6R:1B, 1.2R:1B, and 1.5R:1B. As canopy openness (CO) increases and leaf area index decreases, the proportion of red light in the understory gradually rises. Saplings under the highest CO with a 1.5R:1B had lower leaf area but higher leaf dry matter, starch, carbon, and potassium contents. Metabolite analysis revealed that, under 1.5R:1B light conditions, the upregulation of sucrose synthase (SS) and sucrose-phosphate synthase (SPS) enzyme activities accelerated the consumption of maltose in leaves, led to the accumulation of ribitol and d-glucitol, and increased the levels of organic acids, thereby promoting the accumulation of flavonoids. These findings suggest that 0.6R:1B favors a resource acquisition strategy (rapid growth), while 1.5R:1B leans towards a resource conservation strategy (slow growth). This study provides a new perspective on the effects of light conditions on understory vegetation regeneration.